2022
DOI: 10.3390/ma15020597
|View full text |Cite
|
Sign up to set email alerts
|

Localization Properties of a Quasiperiodic Ladder under Physical Gain and Loss: Tuning of Critical Points, Mixed-Phase Zone and Mobility Edge

Abstract: We explore the localization properties of a double-stranded ladder within a tight-binding framework where the site energies of different lattice sites are distributed in the cosine form following the Aubry–André–Harper (AAH) model. An imaginary site energy, which can be positive or negative, referred to as physical gain or loss, is included in each of these lattice sites which makes the system a non-Hermitian (NH) one. Depending on the distribution of imaginary site energies, we obtain balanced and imbalanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…It was shown that an intermediate regime characterized by the coexistence of localized and extended states at different energies may occur 3,4 . The theoretical findings were confirmed in an experimental realization of a system with a single-particle mobility edge 5 .Recently, in non-Hermitian systems mobility edges have been explored for various 1D tight-binding models [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] . In non-Hermitian systems, in comparison to the Hermitian ones, the mobility edges not only separate localized states from the extended states but also indicate the coexistence of complex and real energies.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…It was shown that an intermediate regime characterized by the coexistence of localized and extended states at different energies may occur 3,4 . The theoretical findings were confirmed in an experimental realization of a system with a single-particle mobility edge 5 .Recently, in non-Hermitian systems mobility edges have been explored for various 1D tight-binding models [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] . In non-Hermitian systems, in comparison to the Hermitian ones, the mobility edges not only separate localized states from the extended states but also indicate the coexistence of complex and real energies.…”
mentioning
confidence: 69%
“…Recently, in non-Hermitian systems mobility edges have been explored for various 1D tight-binding models [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] . In non-Hermitian systems, in comparison to the Hermitian ones, the mobility edges not only separate localized states from the extended states but also indicate the coexistence of complex and real energies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although the behavior of aperiodic chains has been investigated extensively and in great detail, comparatively little work has been dedicated to the case where two or more chains are coupled to each other, forming an aperiodic ladder [11][12][13][14][15]. In this work, we take a step into this realm by analyzing a range of different coupling schemes between two identical one-dimensional Fibonacci chains.…”
Section: Introductionmentioning
confidence: 99%
“…Due to such a non-zero critical point, the system provides different anomalous and divergent features which lead the scientist to proceed further and extract several exceptional properties as well as materialize different new areas in the branch of electronic and phononic transport. Along with AAH modulation [15][16][17][18][19][20][21][22][23][24][25][26], a further constraint can be introduced through hopping dimerization to extract more non-trivial features of the system. The Su-Schrieffer-Heeger (SSH) model [27][28][29][30][31][32][33][34][35][36] is a straightforward example of such kind of topological system.…”
Section: Introductionmentioning
confidence: 99%